2010
DOI: 10.1523/jneurosci.4668-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Individual Stress Vulnerability Is Predicted by Short-Term Memory and AMPA Receptor Subunit Ratio in the Hippocampus

Abstract: Increased vulnerability to aversive experiences is one of the main risk factors for stress-related psychiatric disorders as major depression. However, the molecular bases of vulnerability, on the one hand, and stress resilience, on the other hand, are still not understood. Increasing clinical and preclinical evidence suggests a central involvement of the glutamatergic system in the pathogenesis of major depression. Using a mouse paradigm, modeling increased stress vulnerability and depression-like symptoms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 54 publications
9
69
0
2
Order By: Relevance
“…In a previous study applying a slightly different chronic defeat model, Homer1 expression was also reported to be upregulated in the nucleus accumbens (Berton et al, 2006). Furthermore, microarray data from another study in our lab indicated hippocampal Homer1 to be differentially regulated between stress-resilient and -vulnerable animals (Schmidt et al, 2010), further strengthening the evidence of Homer1 being involved in stress-induced psychopathology. At least on the mRNA level, the effects of chronic stress were specific to the Homer1b/c splice variant, whereas the expression of the immediate early gene Homer1a was not affected.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In a previous study applying a slightly different chronic defeat model, Homer1 expression was also reported to be upregulated in the nucleus accumbens (Berton et al, 2006). Furthermore, microarray data from another study in our lab indicated hippocampal Homer1 to be differentially regulated between stress-resilient and -vulnerable animals (Schmidt et al, 2010), further strengthening the evidence of Homer1 being involved in stress-induced psychopathology. At least on the mRNA level, the effects of chronic stress were specific to the Homer1b/c splice variant, whereas the expression of the immediate early gene Homer1a was not affected.…”
Section: Discussionsupporting
confidence: 69%
“…RNA was isolated from whole hippocampi using the TRIZOL reagent (Invitrogen) as previously described (Schmidt et al, 2010). The quality of the RNA was assessed using an Agilent 2100 Bioanalyzer (Agilent Technologies, Palo Alto, CA).…”
Section: Rna Processingmentioning
confidence: 99%
“…Another important peculiarity of this study is that the facilitating cognitive actions of glucocorticoids were observed in memory tests delivered several hours after treatment [58]. In fact, substantial evidence indicates that when stress or glucocorticoid elevations occur either shortly before or during working memory performance, an impairment is observed [12,59,60].…”
Section: Kinases and Phosphatasesmentioning
confidence: 77%
“…Working memory -as tested in a PFC-dependent Tmaze delayed alternation task -was improved, in a GRdependent manner, when rats were tested at 4 h or 24 h, but not at 48 h after forced-swim stress. Stress and corticosterone increased postsynaptic glutamatergic transmission via GRs -most likely through the observed postsynaptic delivery of AMPARs and NMDARs -in the PFC ( [57]; but note that a negative correlation was recently found between hippocampal GluA2 expression and short-term memory [58]). However, in contrast to the examples discussed previously in this section, the stress/glucocorticoids whose cognitive effects were explored in this latter working-memory study [58] are not those elicited by training, but were instead Box 3.…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 99%
“…Whether our identified biomarkers represent a mere proxy of estrogen sensitivity or are involved in PPD pathophysiology will require further study. TTC9B may be linked to regulation of AMPA receptor levels, which in turn have been shown to be associated with resilience or vulnerability to stress (Schmidt et al, 2010). If the molecular changes exhibited by the biomarkers indicate a biological vulnerability, these may interact with stress occurring in the postnatal period and ultimately lead to depression.…”
mentioning
confidence: 99%